Characteristic of neurogenic secretome under hypoxia: Organoleptic, IL-6 and IL-10 profile - Soetojo, Bagus Wibowo; Wardhana, Teddy Heri; Suroto, Heri (Edelweiss Applied Science and Technology, 2024)
Understanding the physical characteristics and IL-6/IL-10 cytokine levels of neurogenic secretome is crucial for evaluating the effectiveness of stem cell therapy in nerve injury treatment. This study utilized an in vitro experimental design to analyze the organoleptic properties, pH levels, moisture content, and structural features of neurogenic secretome under hypoxia. Electron microscopy was used to examine structural details, while ELISA tests were performed to measure IL-6 and IL-10 cytokine concentrations. The control group exhibited a pale pink color in both liquid and freeze-dried forms, while the neurogenic secretome appeared light orange in liquid form and yellow when freeze-dried. Both samples had a neutral pH of 7.00. The control group showed a higher moisture content (5.510%) compared to the neurogenic secretome (5.099%). Electron microscopy revealed more pores in the neurogenic secretome than in the control (p=0.237). Additionally, cytokine analysis showed significantly lower levels of IL-6 and IL-10 in the neurogenic secretome compared to the control group (p<0.0001). The neurogenic secretome exhibited distinct physical characteristics, including more pores and lower cytokine levels, which may enhance cell proliferation and adhesion, potentially improving its effectiveness in stem cell therapy for nerve injuries. The findings suggest that neurogenic secretome, with its unique properties, could offer advantages in therapeutic applications involving nerve regeneration.